Tersedianya Potensi Suplai Dan Drainasi Persawahan Danda Besar Melalui Revitalisasi Prasarana Hidraulik Tingkat Tersier - L Budi Triadi; Parlinggoman Simanungkalit; Maruddin Fernandus (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2010)
The low agriculture productivity at Danda Besar tidal swamp area is related with the existing watermanagement system which is still at macro and meso level, and not fulfilling the paddy field water supply(micro water management system). Planting is carried out only in the wet season because the insufficientwater management system does not provide available water supply in dry season. Impact of this probleminclude among others that the canal system become shallow and covered by vegetation. Quaternary canalsare also not available. The selected location of this study is the Tertiary T2 Kanan Canalat Danda Jaya, avillage in Kabupaten Barito Kuala, South Kalimantan province. These problems can be solved by watermanagementrevitalizationand micro water management applicationequipped with a water regulator suchas the Flap Gate. This study carrying out a 1 D hydraulic numeric simulation model in five scenarios byapplication of the DUFLOW computer program showed the improvement ofcanal capacity until adequatewaterissuppliedduringneapandspringtide.Thus,farmerscancarryoutaplantingpatterntwiceayearinordertoincreasethecropproductionindexfrom100%to150200%.